Slip rate estimation along the western segment of the Main Marmara Fault over the last 405–490 ka by correlating mass transport deposits. Issue 6 (19th December 2013) - Grall, C.; Henry, P.; Thomas, Y.; Westbrook, G. K.; Çağatay, M. N.; Marsset, B.; Saritas, H.; Çifçi, G.; Géli, L.
Abstract [1] High‐resolution 3‐D seismic data acquired in the Sea of Marmara on the Western High, along the northwestern branch of the North Anatolian Fault (also known as the Main Marmara Fault), shed new light on the evolution of the deformation over the last 500–600 ka. Sedimentary sequences in ponded basins are correlated with glacioeustatic cycles and transitions between marine and low sea/lake environments in the Sea of Marmara. In the 3 × 11 km2 of the 3‐D seismic survey, deformation over the last 405–490 ka is localized along the main fault branch and north of it, where N130°–N140° trending normal faults and N40°–N50° folding accommodated strike‐slip deformation associated with active argillokinesis. There is some evidence that deformation was more distributed further back in the past, at least over the depth range (<600 m below seafloor) of our survey. A N110° basin and buried ridge system were eventually cut by the presently active fault. The southern part of the basin was then uplifted, while the northern part was folded but continued to subside along the fault. A mass transport deposits complex dated between 405–490 ka shows a lateral displacement of 7.7 ± 0.3 km, corresponding to an estimated slip rate of 15.1–19.7 mm/a. We conclude that this strand of the Main Marmara Fault on the Western High has taken up most of the strike slip motion between the Anatolian and Eurasian plates over the last 405 ka at least.